Influence of Experimental Conditions during Synthesis on the Physicochemical Properties of the SPION/Hydroxyapatite Nanocomposite for Magnetic Hyperthermia Application - Dinh Thi Mai Thanh; Nguyen Thu Phuong; Do Thi Hai; Ha Ngan Giang; Nguyen Thi Thom; Pham Thi Nam; Nguyen Trung Dung; Michael Giersig; Magdalena Osial (Magnetochemistry, 2022)
In this work, we report on the fabrication of nanocomposites based on superparamagnetic iron oxide nanoparticles (SPIONs) in combination with hydroxyapatite (HAp) as a platform for drug delivery and magnetic hyperthermia application. First, the influence of experimental conditions such as co-precipitant, bath temperature, and pH on the morphology and magnetic properties of SPIONs was investigated. Then, the superparamagnetic particles were coated with the hydroxyapatite layer for further loading of anticancer drugs, determining the optimal thickness of the HAp shell. The composite was fabricated by the wet chemical process and was characterized by optimizing the experimental conditions of the wiring synthesis to obtain the superparamagnetic spherical material with a high HAp loading as a platform for drug uptake. SEM and TEM studies confirmed the round shape of the magnetic core up to 15 nm in size with a well-defined HAp shell. After checking the material’s superparamagnetic properties, the temperature dependence on time and alternating magnetic field strength was tested and optimized in hyperthermia experiments.